Coupled oxidation resistance and thermal stability in sputter deposited nanograined alloys. Issue 1 (13th November 2018) - Shetty, Pralav P.; Emigh, Megan G.; Krogstad, Jessica A.
Abstract: Abstract : The oxidation behavior of nanograined and coarse-grained alloys may differ significantly. This empirical observation has been justified on the basis of accelerated grain boundary diffusion. However, thermal destabilization of nanograined microstructures studied in model sputter deposited NiCrAl alloys progresses concurrently with the onset of oxidation. This phenomenon makes it challenging to pinpoint the specific contribution of the original grain boundary network. In this study, dilute additions of Y are used to delay the onset of microstructural evolution at elevated temperatures through nanocluster formation and grain boundary pinning. The enhanced microstructural stability resulted in measurably different oxide morphologies during the transient stages of oxidation and slower oxidation rates overall. This coupling between the earliest stages of oxidation and microstructural evolution are directly manipulated to study fundamental oxidation processes in sputtered NiCrAl. Insights gained from this study may ultimately be used to develop novel strategies for improved oxidation resistance in structural alloys.